Geology of the Kharidhunga-Thokarpa area, Central Nepal, Lesser Himalaya - Dahal, Ranjan Kumar; Adhikary, Prakash Chandra (Journal of Nepal Geological Society, 2001)
In the Kharidhunga-Thokarpa area, the rocks of Lower Nawakot Group are exposed. The lowermost unit of the study area is the Kuncha Formation. It is composed of a more than 2,500 m thick monotonous sequence of grey to green phyllite, quartzite, and 'gritty' phyllite. Green-grey quartzite is seen in the upper part of the formation. Small (0.5 mm) garnets of brown colour occur in the upper part of the formation. The Fagfog Quartzite has a sharp contact with the underlying Kuncha Formation and consists of fine- to coarse-grained pure white quartzite with thin to very thin bands of grey and green phyllite. The Dandagaon Phyllite follows the Fagfog Quartzite and contains mainly thin bands of grey-green and dark grey phyllite. The Nourpul Formation is separated from the underlying Dandagaon Phyllite by a yellow quartzite band. The Nourpul Formation consists of dark grey carbonaceous slate and phyllite with some intercalations of calcareous phyllite and calcareous quartzite in the upper part. The augen gneiss, granitic gneiss, and banded gneiss are found within the Nourpul Formation mainly in the eastern part of the study area. The Dhading Dolomite overlies the Nourpul Formation and is found mainly around the Kharidhunga area as wavy and massive beds and lenses of dolomite, magnesite, and talc with sporadic quartzite bands. The rock is highly fractured and crystalline. The Pheda Khola and Ghane Khola Faults have a significant control on the landscape of the study area. The Quaternary deposits of the Kharidhunga area are classified into the Balephi, Thumpakhar, Dandapakhar, Bonch, Rolekharka, and Dangdunge Formations, respectively from bottom to top. Of which, the first two formations correspond to debris flow and river channel deposits, whereas the remaining ones represent the deposits of retreating glacier. Generally, the cohesion and plasticity of these sediments increases with their increasing geological age.